Power measures of athletes in combat sports using a modified rowing ergometer - Zerpa, C.; Johnstone, K.; Sanzo, P.; Przysucha, E. (International Journal of Sports Science, 2013)
Combat sports such as wrestling and mixed martial arts (MMA) require athletes to produce high levels of muscle power to increase athletes` chances of winning during sport competitions. Recently, combat sport athletes in wrestling and MMA began using rowing as a training method because this exercise engages upper and lower extremity muscles of the body and focuses on explosive muscle power. The problem with using rowing as a training technique for athletes in combat sports is that current bases of support designed for rowing ergometers limit the position of the athletes` feet to only a close stance (athletes` feet positioned apart at a distance less than shoulder width). Combat sports in wrestling and MMA, however, require the use of wide (feet positioned apart at a distance slightly wider than shoulder width) or staggered (feet positioned apart at a distance slightly wider than shoulder width and one foot farther forward than the other) stances. Due to this concern, the purpose of this study was to examine the effect of different bases of support (close, wide, and staggered) on athletes` power output when using a Concept2 Rowing Ergometer. Fifteen male combat sport athletes (wrestlers and mixed martial arts athletes) were selected for this study. The athletes completed three exercise sessions in which they were required to row for five minutes in each session with a different base of support (close, wide, and staggered). The power output was measured in watts and the data were analyzed by using a repeated measures ANOVA. The results revealed a significant difference between the close and wide stance. The outcome of this study may have implication for coaches and researchers because it provides an avenue to improve the effectiveness of power training in combat sports when using a Concept2 Rowing Ergometer.